Agents of Change: Modeling Two-Year College English Teachers' Change Resilience and Saturation during COVID and (we hope) Beyond - Suh, Emily K.; Griffiths, Brett M.; Tinoco, Lizbett; Sullivan, Patrick; Snyder, Sarah (Radical Teacher, 2023)
In the face of the pandemic, teachers sought to rapidly incorporate new technologies and maintain or expand meaningful relationships with their students. We created a survey to capture the lived experiences of this moment and bear witness to teachers' frustrations and triumphs during this time. In addition to reports of exteme burnout and emotional labor, we discovered possibilities for changes that contributed to teachers' greater resilience. In this article, we share experiences of change saturation and change resilience to illustrate the conditions we hope to foster in order to sustain the radical teaching practices of teaching with compassion.